National Geographic backyard guide to the birds of North America - Alderfer, Jonathan K. (National Geographic, 2011)
The only comprehensive guide of its kind, this book is for households interested in attracting and identifying birds in their own backyards. Chapters cover all aspects of birding in an easy, accessible way. Vivid illustrations of 150 common species make identification a snap. Tips on feeding, birdhouses, and bird-friendly landscapes show how to attract birds to any environment for optimal viewing. Even children can get in on the action with a section devoted to kid-friendly projects and activities.